Multimorbidity in Older Adults With Cardiovascular Disease - Forman, Daniel E; Maurer, Mathew S; Boyd, Cynthia; Brindis, Ralph; Salive, Marcel E; Horne, Frances McFarland; Bell, Susan P; Fulmer, Terry; Reuben, David B; Zieman, Susan; Rich, Michael W (Journal of the American College of Cardiology, 2018)
Multimorbidity occurs in adults of all ages, but the number and complexity of comorbid conditions commonly increase with advancing age such that cardiovascular disease (CVD) in older adults typically occurs in a context of multimorbidity. Current clinical practice and research mainly target single disease-specific care that does not embrace the complexities imposed by concurrent conditions. In this paper, emerging concepts regarding CVD in combination with multimorbidity are reviewed, including recommendations for incorporating multimorbidity into clinical decision making, critical knowledge gaps, and research priorities to optimize care of complex older patients.